Changes in the acute recovery and stress scale during a high-intensive training period in well-trained cyclists - Feistenauer, C.; Hammes, D.; Skorski, S.; Schwindling, S.; Kellmann, M.; Meyer, T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Underperformance in sports is mainly caused by an imbalance of stress and recovery from training, competition, and lifestyle factors (Kellmann, 2010). To prevent underperformance it is necessary to monitor the acute recovery and stress state. For that purpose a new instrument was developed (Hitzschke et al., 2013), but has not been validated in an intensive micro cycle so far. The aim of the present study was to validate the Acute Recovery and Stress Scale (ARSS) during an intensive training and recovery period in welltrained cyclists. Methods: 28 cyclists (5 w, 23 m, age: 29±7 y) completed an 11-day training camp including performance tests at day 1, day 8 and day 11. Training days consisted of 2 cycling sessions per day (high-intensity-low-volume and low-intensity-high-volume training). Day 8 was followed by two days of recovery. Each morning the ARSS was filled in by all participants. Scales range between 0 (not at all) and 6 (absolutely). 32 adjectives, which express acute feelings, are separated into two categories with each including four scales assessing acute physical, mental, emotional and overall recovery and stress states (Hitzschke et al., 2013). Results: At the latest on day 4 and culminating on day 8 of the training camp the subtests of the ARSS except Emotional Balance/Imbalance revealed significant differences as related to baseline measurement on day 1. Mean differences and standard error between day 1 and 8 in descending order were for stress scales Muscular Strain (-3.10 ± .37 p < .01) Overall Strain (-2.01 ± .23; p < .01), Lack of Activation (-1.20 ± .29; p <.02) and Emotional Imbalance (n.s.), for recovery scales Physical Performance Capability (1.55 ± .30; p < .01), Overall Recovery (1.88 ± .31; p < .01), Mental Performance Capability (1.21 ± .30; p < .03) and Emotional Balance (n.s.). During the two days of recovery all scales returned to baseline again. Discussion: The results indicate that the ARSS is able to monitor acute physical, mental and overall stress and recovery sensitively during a high intense training period in trained cyclists. However, emotional factors did not change over the span of the study. This confirms findings from Koelling et al. (2013) whereby no emotional influences might be expected in training camps, if there is no pressure to perform. It is to be expected that emotional influences change over a prolonged intensive training period. To conclude, the ARSS is able to monitor stress and recovery factors in well trained cyclists.